Forest soil yeasts: Decomposition potential and the utilization of carbon sources. (August 2018) - Mašínová, Tereza; Yurkov, Andrey; Baldrian, Petr
Abstract: Fungi that inhabit forest topsoil can be distinguished into two morphological guilds: filamentous, multicellular fungi and predominantly unicellular yeasts. The nutritional mode of these two groups is expected to differ due to the dependence of yeasts on locally present nutrients. Here we explored the decomposition potential and carbon utilization profiles of dominant yeasts from the temperate forest topsoil. The results indicated that despite taxonomic heterogeneity, yeasts represent a fungal group with a specific nutritional strategy that is dissimilar from other tested fungi. While the efficient decomposition of hemicellulose, cellulose or chitin appeared to be restricted to only a few yeast taxa, carbon source utilization assays indicated that most yeasts could efficiently act as opportunists, utilizing the decomposition products generated by other microbes. Importantly, a large fraction of enzyme activity was associated with yeast cell surfaces indicating their adaptation to generate decomposition products so that they are readily available for intake.